Perspectives of Infant Mortality from African American Community Members - Kalyn M. Renbarger; Sheila Abebe; Jean Marie Place; Elizabeth Goldsby; Gabe Hall; Adam Kroot (Mary Ann Liebert, 2023)
Introduction: Infant mortality (IM) is often used to determine overall population health and well-being. Health disparities exist with African American (AA) infants having higher rates of IM than White infants. The purpose of this study was to examine the knowledge, attitudes, and perceptions of members in an AA community regarding IM, which can be used to develop interventions. Methods: A qualitative descriptive design guided this study. A county in the state of Indiana was the setting from which the researchers enrolled participants in this study. The participants consisted of 16 AA community members who were recruited from a local agency and who had completed an educational program on IM. Through semistructured phone interviews, participants described their understanding of IM. The data analysis of the transcribed interviews was performed via content analysis to yield overall themes from the data. Results: The analysis identified three themes describing AA Community members' perspectives on IM: (1) Shying Away from the Topic of Infant Mortality; (2) Receiving Misinformation from Family Members; and (3) Considering Infant Mortality as Unpreventable. Discussion: The findings of this study suggest that participants avoided the topic of IM, often received misinformation from family members, and believed infant death could not be prevented. Health care providers should have an open and culturally competent discussion about issues of IM, engage family members, and support community-based initiatives and education for members in AA communities.